2009
DOI: 10.1002/stem.77
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Boundary Cap Neural Crest Stem Cell Differentiation After Transplantation

Abstract: Success of cell replacement therapies for neurological disorders will depend largely on the optimization of strategies to enhance viability and control the developmental fate of stem cells after transplantation. Once transplanted, stem/progenitor cells display a tendency to maintain an undifferentiated phenotype or differentiate into inappropriate cell types. Gain and loss of function experiments have revealed key transcription factors which drive differentiation of immature stem/progenitor cells toward more m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…We found no labelling with antibodies that identify specific sensory neurone subtypes (S. Vasilovska and E. N. Kozlova, unpublished observations), indicating that specific stimulation of neuronal differentiation may be necessary to achieve reinnervation of islets from co-transplanted NCSCs. We recently demonstrated that subtype-specific differentiation of NCSCs after transplantation of only neurospheres can be induced by activating specific transcription factors [22]. This approach provides an opportunity to re-innervate islets from differentiated NCSCs in this transplantation setting.…”
Section: Discussionmentioning
confidence: 99%
“…We found no labelling with antibodies that identify specific sensory neurone subtypes (S. Vasilovska and E. N. Kozlova, unpublished observations), indicating that specific stimulation of neuronal differentiation may be necessary to achieve reinnervation of islets from co-transplanted NCSCs. We recently demonstrated that subtype-specific differentiation of NCSCs after transplantation of only neurospheres can be induced by activating specific transcription factors [22]. This approach provides an opportunity to re-innervate islets from differentiated NCSCs in this transplantation setting.…”
Section: Discussionmentioning
confidence: 99%
“…The neurospheres formed by NCSCs isolated from the DRG of E11.5 mice [16] were insulin − (data not shown), proliferated and remained undifferentiated when cultured in PROP [10]. When cultured in DIFF, which differs from PROP by the absence of bFGF and EGF, or when subjected for 2 days to an in vitro differentiation assay [17], the cells differentiated into either GFAP + or β-tubulin III + cells [10]. When islets and neurospheres were co-cultured in PROP for 1 week on glass slides coated with poly-lysine and laminin, axonal length was short (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The DRG preparation included the boundary cap, a transient neural crestderived structure giving rise to the last wave of DRG neurons in development [12][13][14]. The NCSCs are multipotent stem cells that have been shown to generate sensory neurons in vitro [15,16] and glial cells and neurons in vivo after transplantation [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Boundary cap progenitors maintain a state of pluripotency somewhere between that of early NCCs and a Schwann cell progenitor (SCP), though in vitro studies have shown that these cells can even generate multiple CNS subtypes (Coulpier et al, 2009; Zujovic et al, 2010, 2011). These characteristics have led to a number of studies seeking to utilize boundary cap progenitor transplantation in spinal cord, peripheral nerve, and dorsal root injury paradigms (Aldskogius et al, 2009; Aquino et al, 2006; Trolle, Konig, Abrahamsson, Vasylovska, & Kozlova, 2014; Zujovic et al, 2010, 2011). …”
Section: Boundary Capmentioning
confidence: 99%